1982
DOI: 10.1111/j.1651-2227.1982.tb09513.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Adaptation to Extrauterine Circulation

Abstract: Left ventricular systolic time intervals (STI) were recorded by non-invasive technique from the axillary artery in fifteen normal newborns from 10-15 min to 70-74 hours after birth. The observed changes in the different STI could almost entirely be related to changes in the isovolumic contraction time (ICT). At the early postnatal recording ICT was only 21.0 msec suggesting an enhanced left ventricular performance compared to prenatal observations. During the following hours ICT increased to 31.6 msec which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…At present there is no available non-invasive technique for accurate quantitation of the ductus flow, but studies of left ventricular systolic time intervals also seem to show early disappearance of a haemodynamically important ductus shunt. 27 The sleep/wake state may also influence left ventricular output. At the first two recordings the infants were awake and left ventricular output was high, whereas at the two last recordings most infants were asleep and left ventricular output was lower.…”
Section: Discussionmentioning
confidence: 99%
“…At present there is no available non-invasive technique for accurate quantitation of the ductus flow, but studies of left ventricular systolic time intervals also seem to show early disappearance of a haemodynamically important ductus shunt. 27 The sleep/wake state may also influence left ventricular output. At the first two recordings the infants were awake and left ventricular output was high, whereas at the two last recordings most infants were asleep and left ventricular output was lower.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of changes in left ventricular systolic time intervals (STI) in term infants during the first three days after birth (9), we suggested that the short preejection intervals seen immediately after birth reflected increased left ventricular volume load. Normalization of these intervals 4-6 hours after birth was thought to coincide with ductal closure and reduced volume load to the left vent ricle .…”
mentioning
confidence: 98%
“…Again, in the majority of these investigations an increase of the end-diastolic left ventricular volume [31,33,69] and of myocardial performance [45,46,48,68] was observed in the human newborn after birth while one study yielded contradictory results [18].…”
mentioning
confidence: 99%